SUBJECT: PSYCHOLOGICAL APPEARANCES OF THE EMOTIONAL STATE IN ADOLESCENTS - Xudoyqulova , Shoira (Educational Research in Universal Sciences, 2023)
In this article, the mental characteristics of adolescence, mental and emotional development, personality characteristics during this period are highlighted. The formation of their consciousness and worldview, taking into account the age and psychological characteristics of adolescent children, working with them, and developing the skills to solve problematic situations will be discussed.